2014
DOI: 10.1016/j.yfrne.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive neuroendocrine dysfunction in polycystic ovary syndrome: Insight from animal models

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrinopathy with elusive origins. A clinically heterogeneous disorder, PCOS is likely to have multiple etiologies comprised of both genetic and environmental factors. Reproductive neuroendocrine dysfunction involving increased frequency and amplitude of gonadotropin-releasing hormone (GnRH) release, as reflected by pulsatile luteinizing hormone (LH) secretion, is an important pathophysiologic component in PCOS. Whether this defect is primary or secondary to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 168 publications
0
25
0
1
Order By: Relevance
“…Moreover, another study reported that glucose tolerance was normal in PNA mice [26]. It has been suggested that the absence of significant metabolic dysfunction or obesity in PNA mice signifies it as a lean PCOS model [73] and could be useful for representing the condition in some PCOS women who lack metabolic impairments [74]. Alternatively, the PNA model may represent a milder form of PCOS across the PCOS spectrum.…”
Section: Comparison With Other Mouse Pcos Modelsmentioning
confidence: 99%
“…Moreover, another study reported that glucose tolerance was normal in PNA mice [26]. It has been suggested that the absence of significant metabolic dysfunction or obesity in PNA mice signifies it as a lean PCOS model [73] and could be useful for representing the condition in some PCOS women who lack metabolic impairments [74]. Alternatively, the PNA model may represent a milder form of PCOS across the PCOS spectrum.…”
Section: Comparison With Other Mouse Pcos Modelsmentioning
confidence: 99%
“…Reproduction in all systems is heavily influenced by metabolism and nutrition [1,2]. Several human reproductive disorders have been linked to malnutrition, diabetes, and obesity [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, polycystic ovarian syndrome (PCOS), the most common anovulatory cause of infertility 71 affecting >100 million women worldwide, is associated with a dysregulation of the normal pattern of LH secretion 72 . Whether the origin of this multi-factorial disorder is at the level of the hypothalamic-pituitary axis is unknown 73 , but PCOS is characterized by increases in GnRH pulse frequency and sensitivity of the pituitary gland to the neurohormone 74,75 . Consequently, potential interventions that modify the dynamics of GnRH output, its transport to the ME or its 79 .…”
Section: H3] Clinical Relevancementioning
confidence: 99%